2017
DOI: 10.1177/0267659117735883
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the depth of isoflurane anaesthesia during cardiopulmonary bypass

Abstract: In conclusion, in patients undergoing heart surgery with CPB, the findings of this study indicate that, whilst oxygenator exhaust concentrations were significantly associated with arterial concentrations of isoflurane, neither had any association with the BIS scores, whereas body temperature has moderate positive correlation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
2
5
0
2
Order By: Relevance
“…19,20 Both studies had almost identical methodology as the present study, but while the main study found a significant correlation between oxygenator exhaust and arterial isoflurane concentration indicating that inaccuracy in gas measurement may not have been the cause of failure to detect a correlation in the present study, the sub-study did not find a correlation. 19,20 The most important difference in methodology between the main study and the sub-study is that because patients from four anaesthetists were recruited, a range of doses of isoflurane from 1% to 2.5% was administered rather than a fixed dose of 2.5% in the sub-study because it used only patients from one anaesthetist. Thus, using a range of doses rather than a fixed dose made detecting a true signal between oxygenator exhaust and arterial blood concentrations of isoflurane possible using a small study population size.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…19,20 Both studies had almost identical methodology as the present study, but while the main study found a significant correlation between oxygenator exhaust and arterial isoflurane concentration indicating that inaccuracy in gas measurement may not have been the cause of failure to detect a correlation in the present study, the sub-study did not find a correlation. 19,20 The most important difference in methodology between the main study and the sub-study is that because patients from four anaesthetists were recruited, a range of doses of isoflurane from 1% to 2.5% was administered rather than a fixed dose of 2.5% in the sub-study because it used only patients from one anaesthetist. Thus, using a range of doses rather than a fixed dose made detecting a true signal between oxygenator exhaust and arterial blood concentrations of isoflurane possible using a small study population size.…”
Section: Discussionsupporting
confidence: 51%
“…While this finding conflicts with three, two other studies have also been unable to detect a relationship between oxygenator exhaust and arterial blood concentration of volatile anaesthetic agent. 1620 An important weakness of this part of the present study is that several different anaesthetic gas monitor modules were used, and although the modules’ accuracy are checked annually and recalibrated if required, it cannot be excluded that they were inaccurate during the period of study and that using multiple modules introduced variance. If the study was to be repeated, then these sources of variance could be reduced by using a single gas analyser module and confirming its accuracy during the period of study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During CPB, the concentration of the volatile anaesthetic in the oxygenator exhaust line should be monitored. 256 It has been demonstrated that this concentration correlates well with the arterial concentration, 250,260 although others dispute this. 250 During CPB, isoflurane and sevoflurane can cause hypotension by vasodilation.…”
Section: Volatile Anaestheticsmentioning
confidence: 97%
“…Recently, a nociception index (qNOX) measures the probability of the patient to respond to external noxious stimuli, and thus, providing an objective measurement of the patient’s nociception or analgesia state. 5,6 At present, many studies have focused on qCON or BIS, and similar indices monitoring for hypnotic depths, in particular for CPB, 79 but only a few studies have focused on monitoring for analgesic depth, 10 in particular from EEG-derived monitoring, such as the qNOX. The study hypothesized that qNOX, in combination with the qCON or BIS, can effectively reflect the analgesia and hypnosis levels, particularly, in the CPB cardiac surgery.…”
Section: Introductionmentioning
confidence: 99%